Impact of diet on the risk of breast cancer - Kamila Sawicka; Jarosław Koza (Kazimierz Wielki University, 2018)
This work concerns the issue of women nutrition in the prevention of breast cancer, which is the most common malignant tumour and the second death related cancer of the females. The aim of the work is to present types of diets, the use of which can reduce the risk of breast cancer. The article refers the chemopreventive action of substances naturally present in foods such as plant polyphenols, dietary fiber and polyunsaturated omega-3 fatty acids. The presented review confirms that they are able to reverse, inhibit or delay the process of carcinogenesis, as a result of the apoptosis initiation, anti-inflammatory and antioxidant effects and by inhibition of angiogenesis and proliferation. The described compounds may also reduce estrogen concentration and prevent the development of obesity. Most of the experiments carried out so far prove that overweight and obesity, excessive consumption of products with a high glycemic index, alcohol and red meat are factors contributing to the occurrence of breast cancer. However, not all epidemiological data are unambiguous in this matter. Mediterranean, vegetarian, Asian and low glycemic index diets, through the synergistic interaction of nutrients contained in them, most effectively reduce the risk of breast cancer.